Water footprint and economic water productivity of citrus production: a comparison across three river valleys in the Eastern Cape Milands - Danckwerts, Lindsay (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2020)
South Africa is a semi-arid, water scarce country. The nation has suffered a spate of severe droughts in several regions in recent years, which have significantly impacted the country's economy. Global warming, population growth, and rising demand for water intensive products are only expected to intensify water supply problems in the future. The agricultural industry is the largest consumer of water in South Africa, accounting for the majority of total surface water withdrawals. As such, the agricultural sector is faced with complex and difficult management decisions in the face of a potential water supply crisis. The water footprint (WF) and economic water productivity (EWP) of citrus production across three river catchments located in the Eastern Cape Midlands (situated in the vicinity of the settlements of Adelaide, Cookhouse and Fort Beaufort respectively) were calculated and compared. In the long-term average (LTA), blue WF weighted across all three regions accounted for the greatest proportion of total WF (53%), followed in turn by green and grey WF (30% and 17% respectively). LTA blue and grey WF was lowest in the Adelaide region, while green WF was smallest in the Fort Beaufort region. Blue, green and grey WF were found to be greatest in the Cookhouse region. LTA EWP was greatest in the Fort Beaufort region and smallest in the Adelaide region. Of all variety groups assessed, lemons were found to have the lowest LTA crop water use and blue, green and grey WF when considering citrus production averaged across all three study regions. Satsumas has the second smallest LTA blue, green and grey WF, followed by navels, mid-season mandarins, and finally, late mandarins. Lemons had the greatest LTA EWP of all varieties, followed in turn by satsumas, late mandarins, mid-season mandarins and navels. Blue crop water use was consistently lowest in the designated wet year and highest in the dry year. However, this same trend was not necessarily true for WF findings. WF and EWP are useful indicators of water use which can be used to help guide complex water management decisions. However, these indicators are single-factor productivity measures applied in a multi-factor environment. It is therefore important that factors outside of water use are considered when making water management decisions. Moreover, it is important to examine the impact that the various components making up WF and EWP have on the resultant figures, rather than merely considering the superficial results themselves. Factors such as CWU, orchard maturity, crop choice, potential yield, climate, irrigation system, economic return, water allocation and water availability should all be taken into account.
Keywords: Water in agriculture -- South Africa -- Eastern Cape; Water consumption -- South Africa -- Economic aspects; Water supply, Agricultural -- South Africa -- Eastern Cape; Citrus fruit industry -- South Africa -- Eastern Cape